Phenomenological-Experience Exercise of Collaborative Teaching in Anthropology of Corporealities - Rostagnol, Susana; Calisto Echeveste, Emilia (Ciencias Sociales y Educación, 2020)
This paper highlights the findings registered during the grade course Anthropology of the Body of Universidad de la República (Uruguay) in which some performative premises were proposed to the students. The goal was introducing activities that involved their direct experience in the curriculum, specifically within the modules related to cultural phenomenology, embodiment, and fieldwork as an incarnated activity. One of the transversal axes within the course was the relativist vision on the construction of the body in western culture. For this reason, some activities were thought for, in a diverse grade, positioning the group in a certain methodological 'uncomfortableness'. For the design of these premises, the project was aided by observations and results from ethnographic research in a contemporary dance school (especially some techniques observed in the research and creation instances). The main conclusion of this work is that hybridizations between dance and anthropology adapted in a didactic manner in experiential premises are useful for widening the anthropological knowledge for better preparing anthropologist for fieldworkand for propitiating more democratic exchanges within the classroom.
Keywords: anthropology of the body; teaching; performative premises; phenomenal- corporeal didactics; dance